Punching Shear Behaviour of FRP Strengthened Flat Slab With and Without Geo-Grid - Kumar, Rishabh (My University, 2017)
The upgradation of the building to satisfy the current demand and to improve the performance of weaker sections of buildings, requires advanced techniques. In particular the lesser reinforcement ratio in flat slabs are prone to punching shear failure when the building is upgraded It is very difficult to increase the percentage of reinforcement in the existing slab. It requires external strengthening using conventional or advanced technique. The conventional technique increases the cross sectional size and is time consuming and it also effects the adjacent structures element performance. FRP is a proven material in strengthening work. This study is mainly focussed on the use of GFRP and BFRP in uni-directional and bi-directional to improve the punching shear behaviour of flat slabs with different reinforcement ratios. In order to reduce the strengthening area required, geo grid as reinforcement to FRP is also evaluated only using FRP in UD (uni-direction). The load deflection, stiffness and energy dissipation, crack pattern and failure pattern are the parameters that are evaluated.
Master of Engineering -Structural Engineering
Keywords: Punchning Shear; Geogrid; Crack Pattern; BFRP; GFRP